The emerging roles of deubiquitinases in plant proteostasis. Issue 2 (5th August 2022) - Skelly, Michael J.
Abstract: Proper regulation of protein homeostasis (proteostasis) is essential for all organisms to survive. A diverse range of post-translational modifications (PTMs) allow precise control of protein abundance, function and cellular localisation. In eukaryotic cells, ubiquitination is a widespread, essential PTM that regulates most, if not all cellular processes. Ubiquitin is added to target proteins via a well-defined enzymatic cascade involving a range of conjugating enzymes and ligases, while its removal is catalysed by a class of enzymes known as deubiquitinases (DUBs). Many human diseases have now been linked to DUB dysfunction, demonstrating the importance of these enzymes in maintaining cellular function. These findings have led to a recent explosion in studying the structure, molecular mechanisms and physiology of DUBs in mammalian systems. Plant DUBs have however remained relatively understudied, with many DUBs identified but their substrates, binding partners and the cellular pathways they regulate only now beginning to emerge. This review focuses on the most recent findings in plant DUB biology, particularly on newly identified DUB substrates and how these offer clues to the wide-ranging roles that DUBs play in the cell. Furthermore, the future outlook on how new technologies in mammalian systems can accelerate the plant DUB field forward is discussed.